Hybrid MoS2/PEDOT:PSS transporting layers for interface engineering of nanoplatelet-based light-emitting diodes. Issue 26 (14th June 2021) - Sorrentino, Roberto; Worsely, Robyn; Lagonegro, Paola; Martella, Christian; Alieva, Adriana; Scavia, Guido; Galeotti, Francesco; Pasini, Mariacecilia; Dubertret, Benoit; Brovelli, Sergio; Molle, Alessandro; Casiraghi, Cinzia; et al.
Abstract : The incorporation of MoS2 nanosheets in well-known PEDOT:PSS water solution, and used as a hole transporting layer in nanocrystal light-emitting diodes, works as a performance booster in unpackaged devices under ambient conditions. Abstract : Colloidal semiconductor nanoplatelets (NPLs) are a subgroup of quantum confined materials that have recently emerged as promising active materials for solution processed light-emitting diodes (LEDs) thanks to their peculiar structural and electronic properties as well as their reduced dimensionality. Nowadays, the conventional structure for NPL-based LEDs makes use of poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) as a hole transporting layer (HTL). This is a well-known conjugated conductive polymer because it leads to high LED efficiency, though it has limited stability in air due to its intrinsic acidity and hygroscopicity. Here, we develop a nanocomposite aqueous ink, obtained by blending commercial PEDOT:PSS with water-based, stable and highly concentrated molybdenum disulfide (MoS2 ) nanosheets, obtained via liquid phase exfoliation (LPE), which is suitable as a HTL for solution processed NPL-based LEDs. We demonstrate that the MoS2 additive effectively works as a performance booster in unpackaged devices, thereby prolonging the lifetime up to 1000 hours under ambient conditions. Moreover, the addition of MoS2 induces a modification of the anode interface properties, including a change in the work function and a significant enhancement of the permittivity of the HTL.